Effect of Photoperiod on the Production of Chukar Partridges (Alectoris chukar) - Alva, V.I.A.; Quintana , L.J.A.; Gonzales-Rebeles, I.C.; Gonzalez, A.M. (International Journal of Poultry Science, 2015)
This study evaluated the effect of variations in photoperiod duration on production indicators such as amount of eggs-laid and weight in chukar partridges (Alectoris chukar). Ninety individuals were divided into groups of 3 males and 7 females per cage (9 cages). Three different photoperiod treatments were used (18, 16 and 14 h light) with three repetitions per treatment. Males and females were randomly selected for each group. Means between treatments were compared using ANDEVA with Tukey’s multiple comparisons in a GLM using the SAS V.8.0 software package. The following variables were evaluated during 18 production weeks: egg weight (EW), egg mass (EM), eggs per female (EF) and laying percentage (LP). Significant differences (p0.05) were found in the remaining parameters between treatments. There was an improvement of all production variables at the smallest photoperiod (14 h) even though only EW was statistically significant.